Kualitas Produk Terhadap Kepuasan Konsumen Fudia Bakery Bandar Lampung - Desi Derina Yusda (Business and Enterpreneurship Journal (BEJ), 2023)
The current marketing concept places consumers as the main concern. More and more companies produce products with the same types and uses, but nowadays consumers are also more selective and critical in choosing products. Consumers no longer buy products based on the physical product, but consumers see the quality of the product. The purpose of this study was to determine the effect of product quality on consumer satisfaction at Fudia Bakery Bandar Lampung. The population in this study were consumers of Fudia Bakery Bandar Lampung with a total sample of 100 respondents using incidential sampling techniques, primary data collection using questionnaires and secondary data collection using literature study and documentation. Testing the hypothesis in this study using double linear regression with the results of product quality has a significant effect on customer satisfaction Fudia Bakery Bandar Lampung. The coefficient of determination obtained is 76.6%, which indicates that product quality has the ability to explain customer satisfaction, while the remaining 23.4% can be explained by variables or other factors not examined in this study. Keywords: Product Quality, Customer Satisfaction, Features, Durability